Pendidkan Pendidikan Akidah Akhlak dalam Membentuk Karakter Siswa - Muhammad Feby Parnanda (Permata : Jurnal Pendidikan Agama Islam, 2021)
From an Islamic perspective, morality or morals have a high position. Thus the high moral position in Islam until the Muhammad SAW make it as a barometer of faith. He said, â€œThe most perfect believer of his faith is the best in his moralsâ€ (HR. Abu Danwud and Tirmidzi. In Islam, morality is strongly related to the faith and is not separated from it. The relationship between faith and morality is also evident in the Muhammad SAW briefings about morality. He often attributes faith in God and the Last Day to Morals. When a person has a high orientation and ideals that is the pleasure of God, then by itself he will consider low anything that is contrary to those ideals that are all deeds or attributes hated by God. Islamic morals have several special features and characteristics that distinguish them from other moral systems. Among the characteristics of Islamic morality are: (a) Rabbaniyah or converted to The Lord (God), (b) Insaniyah (humane), (c) Syumuliyah (universal and encompassing all life), and (d) Wasathiyah (middle attitude). One of the things emphasized in Islam is that moral education must begin from an early age because childhood is the most conducive time to instill good habits. Abstrak Dalam perspektif Islam, akhlak atau moral memiliki kedudukan yang tinggi. Demikian tingginya kedudukan akhlak dalam Islam hingga Muhammad SAW menjadikannya sebagai barometer keimanan. Beliau bersabda, â€œOrang mukmin yang paling sempurna imannya adalah yang paling baik akhlaknya.â€ (HR. Abu Dawud dan Tirmidzi). Dalam Islam, akhlak sangat terkait dengan keimanan dan tidak terpisah darinya. Keterkaitan antara iman dengan akhlak juga terlihat jelas pada pengarahan-pengarahan Muhammad SAW tentang akhlak. Beliau sering sekali mengaitkan keimanan kepada Allah dan hari akhir dengan akhlak. Ketika seseorang memiliki orientasi dan cita-cita yang tinggi yaitu ridha Allah, maka dengan sendirinya ia akan menganggap rendah apa saja yang bertentangan dengan cita-cita tersebut yaitu seluruh perbuatan atau sifat yang dibenci oleh Allah. Akhlak Islami memiliki beberapa keistimewaan dan ciri-ciri khusus (karakteristik) yang membedakannya dari sistem akhlak lainnya. Di antara karakteristik akhlak Islami tersebut adalah: (a) Rabbaniyah atau dinisbatkan kepada Rabb (Tuhan), (b) Insaniyah (bersifat manusiawi), (c) Syumuliyah (universal dan mencakup semua kehidupan), dan (d) Wasathiyah (sikap pertengahan). Suatu hal yang ditekankan dalam Islam adalah pendidikan akhlak wajib dimulai sejak usia dini karena masa kanak-kanak adalah masa yang paling kondusif untuk menanamkan kebiasaan yang baik.